2017
DOI: 10.1002/chem.201700105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bromoaluminate Ionic Liquids

Abstract: Twelve bromoaluminate based ionic liquids (ILs) were synthesized and characterized by IR, Raman, and NMR spectroscopy, as well as single crystal X-ray diffraction in part. Their principal physicochemical properties including melting points, conductivities, viscosities, and densities were determined and compared with related ILs. The influence of the cation and anion on the physicochemical properties are discussed. The [AlBr ] based salts are-with one exception-solid at room temperature, while the compounds bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 218 publications
(121 reference statements)
1
17
0
Order By: Relevance
“…The room-temperature potentiostatic electrodeposition of Al was carriedo ut at ap otentialo fÀ400 mV for 18 ho naCu substrate. [46] The AlCl 3 /BuIm system AlCl 3 -basedm ixturesw ere synthesized to investigate the influence of the aluminumh alide on the symmetric and asymmetric cleavage products and hence the differences between the two systems. The energydispersive X-ray (EDX) spectrum shows peaks of the electrodepositeda luminuma nd small amounts of carbon,o xygen, and copper( see Figure 14 ca nd Figure S37 of the Supporting Information).I nc onclusion, microcrystallinea luminum can be depositede lectrochemically from an eat Lewis acidic mixture of the system AlBr 3 /BuIm {x(AlBr 3 ) = 0.60}.…”
Section: Cyclic Voltammetry and Potentiostatic Electrodepositiono Falmentioning
confidence: 99%
“…The room-temperature potentiostatic electrodeposition of Al was carriedo ut at ap otentialo fÀ400 mV for 18 ho naCu substrate. [46] The AlCl 3 /BuIm system AlCl 3 -basedm ixturesw ere synthesized to investigate the influence of the aluminumh alide on the symmetric and asymmetric cleavage products and hence the differences between the two systems. The energydispersive X-ray (EDX) spectrum shows peaks of the electrodepositeda luminuma nd small amounts of carbon,o xygen, and copper( see Figure 14 ca nd Figure S37 of the Supporting Information).I nc onclusion, microcrystallinea luminum can be depositede lectrochemically from an eat Lewis acidic mixture of the system AlBr 3 /BuIm {x(AlBr 3 ) = 0.60}.…”
Section: Cyclic Voltammetry and Potentiostatic Electrodepositiono Falmentioning
confidence: 99%
“…The melting point of the [AlBr 4 ] − salts are usually the highest for all four anions. Thus, we synthesized and characterized a series of bromoaluminate ILs with the cations ethyl‐dimethyl‐propyl‐ammonium ([N 1123 ] + ), butyl‐dimethyl‐propyl‐ammonium ([N 1134 ] + ), butyl‐diethyl‐methyl‐ammonium ([N 1224 ] + ), triethyl‐pentyl‐ammonium ([N 2225 ] + ), triethyl‐pentyl‐phosphonium ([P 2225 ] + ) and 1‐hexyl‐3‐methyl‐imidazolium ([C 6 MIm] + ) in previous work . Unfortunately, all cations – with the exception of [C 6 MIm] + – led to solid [AlBr 4 ] − salts with melting points between 35 and 117 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, all cations – with the exception of [C 6 MIm] + – led to solid [AlBr 4 ] − salts with melting points between 35 and 117 °C. However, we could potentiostatically electrodeposit microcrystalline Al on a Cu substrate from the IL [C 6 MIm][Al 2 Br 7 ] . In addition, chronoamperometric experiments of [C 6 MIm][Br 9 ] and [C 6 MIm][Br 3 ] showed that the ILs conduct continuous current at positive potentials and cyclic voltammetry revealed an immediate increase of current without a defined oxidation peak at positive potentials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations